Humor sebagai Mediasi Konflik Digital: Analisis Wacana Kritis @NUgarislucu - Risa Pramita Wilda Fitria; Nyimas Ma'rifatillah (NAHNU: Journal of Nahdlatul Ulama and Contemporary Islamic Studies, 2026)
This study focuses on the X account @NUgarislucu as a representation of the Nahdlatul Ulama (NU) community that employs humor as an alternative discursive practice. The study examines how the discursive structure of humor functions as digital conflict mediation. Data were collected through X advanced search using the operator "from:nugarislucu" from January 1, 2016 to May 3, 2026, with filters of minimum 5,000 likes and 250 replies. From these results, the top 7 most relevant posts related to conflict resolution were selected for analysis. Using a qualitative approach and Teun A. van Dijk's critical discourse analysis on textual, socio cognitive, and contextual dimensions, the findings demonstrate that humor operates as a soft power strategy through indirect satire, in group solidarity reinforcement, and diversion of sensitive issues into laughter. This study contributes a conceptual model of humor as an informal, culturally grounded peace infrastructure in digital spaces. It recommends integrating cultural discursive strategies into digital religious moderation policies.   Fokus kajian adalah akun X @NUgarislucu sebagai representasi komunitas Nahdlatul Ulama (NU) yang memanfaatkan humor sebagai praktik diskursif alternatif. Penelitian ini bertujuan mengkaji bagaimana struktur wacana humor berfungsi sebagai mediasi konflik digital. Data dikumpulkan melalui pencarian lanjutan X dengan operator "from:nugarislucu" pada periode 1 Januari 2016 sampai 10 Mei 2026, serta filter minimal 5.000 likes dan 250 replies. Dari hasil filter tersebut, dipilih 7 unggahan teratas yang paling relevan dengan tema resolusi konflik untuk dianalisis. Dengan menggunakan pendekatan kualitatif dan analisis wacana kritis model Teun A. van Dijk pada dimensi teks, kognisi sosial, dan konteks sosial, temuan menunjukkan bahwa humor berfungsi sebagai strategi soft power melalui sindiran tidak langsung, penguatan solidaritas kelompok internal, dan pengalihan isu sensitif ke ranah tawa. Kontribusi penelitian ini adalah model konseptual humor sebagai infrastruktur perdamaian informal berbasis budaya di ruang digital